A case study of adolescent believes and intentions in the use of condom in Bukit Bintang - Suhaimi, Nor Suhaida; Salim, Siti Suria (Faculty of Educational Studies, Universiti Putra Malaysia, 2013)
In Malaysia, the issue of condom is still considered a taboo. Discussing and promoting the use of condom might be seen as against the culture and religiously sensitive. But with the knowledge that Malaysian adolescents had sexual intercourse for the first time at the early age of 23 (Durex, 2012) it is important to realize that the use of condom could protect human from HIV or others STI during sexual intercourse (Davis & Weller, 1999). This study is to explain and understand adolescents in Bukit Bintang believe towards the availability and intention of using of condom during sexual intercourse. I looked at the adolescent self efficacy, barriers of using condom and perceived benefit from using condom as the factors that influence their belief and intention of using condom. My research participants are selected 60 adolescents aged 14-19 years old at Bukit Bintang District. The data collected from the questionnaire distributed were analyzed using SPSS version 21. My findings reveal that the adolescents have no consistency in using condom during sexual intercourse with only 43.3% would refuse to have sexual intercourse without condom, 38.3% would insist on using condom and 35% would have sexual intercourse if there is no condom available. Analyzing the barriers, more than three quarter of the respondents (76.7%) confessed they would be embarrassed to buy condom while 23.3% disagreed with that statement, even though 66.7% of the respondents agreed that condom is easy to get while 33.3% did not think that way and about 63.3% of the respondents agreed that buying condom is not a crime while 36.7% disagreed with this statement. Looking at the perceived benefit of using condom, majority of the respondents agree that condom is an effective way to prevent unwanted pregnancy (58.3%), protect against HIV (60%) and STIs (58.3%). This positive belief could initiate the use of condom. This study could give the direction in understanding the adolescent belief and intention of using condom, which could help predict adolescent sexual behaviour.